Auxin-Induced Modulation of ETTIN Activity Orchestrates Gene Expression in Arabidopsis. Issue 8 (13th August 2017) - Simonini, Sara; Bencivenga, Stefano; Trick, Martin; Østergaard, Lars
Abstract : ETTIN translates changes in auxin levels into diverse transcriptional outcomes to control specific processes during Arabidopsis plant development. Abstract: The phytohormone auxin governs crucial developmental decisions throughout the plant life cycle. Auxin signaling is effectuated by auxin response factors (ARFs) whose activity is repressed by Aux/IAA proteins under low auxin levels, but relieved from repression when cellular auxin concentrations increase. ARF3/ETTIN (ETT) is a conserved noncanonical Arabidopsis thaliana ARF that adopts an alternative auxin-sensing mode of translating auxin levels into multiple transcriptional outcomes. However, a mechanistic model for how this auxin-dependent modulation of ETT activity regulates gene expression has not yet been elucidated. Here, we take a genome-wide approach to show how ETT controls developmental processes in the Arabidopsis shoot through its auxin-sensing property. Moreover, analysis of direct ETT targets suggests that ETT functions as a central node in coordinating auxin dynamics and plant development and reveals tight feedback regulation at both the transcriptional and protein-interaction levels. Finally, we present an example to demonstrate how auxin sensitivity of ETT-protein interactions can shape the composition of downstream transcriptomes to ensure specific developmental outcomes. These results show that direct effects of auxin on protein factors, such as ETT-TF complexes, comprise an important part of auxin biology and likely contribute to the vast number of biological processes affected by this simple molecule.